"Hey, by the Way, I'm Transgender": Transgender Disclosures as Coming Out Stories in Social Contexts among Trans Men. (September 2021) - Kade, Tristen
Connecting theories of identity formation and coming out with impression management, this research highlights that transgender disclosures are not static. Rather, disclosures are continuously mediated by various contextual concerns, ranging from accurate gender recognition, discrimination and stigmatization, the cultivation of emotional and physical intimacy, alerting people of the bodily changes, and understandings of how bodies will be perceived. Through 20 interviews with trans men, I found that they manage their trans identity through two tactics: symbolic disclosure and disclosure avoidance . Disclosure patterns reveal a twin force shaping disclosures: Trans men want gender recognition and/or to strengthen relationships while simultaneously avoiding potential violence, discrimination, and stigmatization. This research contributes to sociological scholarship on identities and disclosure more broadly by elucidating some ways trans men strategically negotiate disclosures based on a variety of concerns.